Scale-up research in a dual fluidized bed gasification process - Narobe, Miha (Acta chimica slovenica, 2015)
A successful co-gasification of plastics and biomass was achieved in the 100 kW dual fluidized bed (DFB) gasification pilot plant. The results of a pilot plant experiment were used as a sound basis for scale-up prediction to 750 kW semiindustrial DFB plant. By an eightfold increase of mass and heat flows a rather simplified co-gasification process was predicted. Namely, the losses occurring in gasification plants are expected to be relatively smaller in larger plants. The effect of decreased losses was studied with an equilibrium model. Three different situations were simulated with the following fixed values of losses: 70 kW, 115 kW and 160 kW. The model showed an increase in fuel conversion when losses were reduced.
Keywords: dual fluidized bed reactor; gasification; scale up; simulacije; simulation; uplinjanje; uplinjevalnik z dvojnim lebdečim slojem